2014
DOI: 10.1002/ep.12029
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methylene blue from an aqueous solution using a cucurbituril polymer

Abstract: This article presents a study on the batch adsorption of methylene blue (MB) in an aqueous solution onto a cucurbituril polymer (CP) in order to explore its potential use as an adsorbent for dye removal from wastewater. Equilibrium studies showed that MB had a high affinity in a basic medium, but decreased as solution pH decreased. The adsorption of MB decreased with an increase in ionic strength for all four types of cations (Na+, K+, Mg2+, and Ca2+). The pseudo first‐order, pseudo second‐order kinetic model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Compared with the reported works on CB[ n ]-based absorbents [3436], the maximum adsorption capacity of MB by PCL/CB[7] nanofibrous membranes is relatively low. The unexpected low adsorption capacity for MB should be mainly ascribed to the weak binding between CB[7] and MB in ethanol, as in non-aqueous solvents the hydrophobic effect is tremendously weakened.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Compared with the reported works on CB[ n ]-based absorbents [3436], the maximum adsorption capacity of MB by PCL/CB[7] nanofibrous membranes is relatively low. The unexpected low adsorption capacity for MB should be mainly ascribed to the weak binding between CB[7] and MB in ethanol, as in non-aqueous solvents the hydrophobic effect is tremendously weakened.…”
Section: Resultsmentioning
confidence: 56%
“…According to the comparison of correlation coefficients R 2 , it is apparent that the experimental equilibrium adsorption data of MB by PCL/CB[7] nanofibrous membranes are better fitted with the Langmuir isotherm model. Therefore, it is easily concluded that the adsorption of MB took place at specific homogeneous sites within the nanofibrous membrane and formed a monolayer coverage of MB at the surface of the nanofibrous membrane [34].…”
Section: Resultsmentioning
confidence: 99%
“…New environmentally friendly adsorbents are also being developed and have also been tested for the removal of MB. This is the case for Cucurbit[n]uril (CB[n]) attached to a carrier, to allow its use for the adsorption of cationic dyes . Following this line, the direct use of sewage sludge as an absorbent whenever possible may be of great interest since the reduction in costs is significant and the relatively high adsorption capacity of this sort of material has been widely proven (above 100 mg g −1 for pyrolyzed and dehydrated sewage sludge) .…”
Section: Introductionmentioning
confidence: 99%
“…22 CBs have the structure of a hydrophobic cavity with identical carbonylfringed portals, which makes them have great potential in the field of adsorption. 23 For instance, there have been reports about the adsorption of sulfamonomethoxine antibiotics, 22 gases, 24 oils, 25 humic acid, 26 and methylene blue 27 with CBs and their derivatives. In our previous work, a CB [6] pseudorotaxane was employed to modify a poly(glycidyl methacrylate-co-ethylene dimethacrylate) monolithic column and applied to the efficient enrichment of nitroaromatics.…”
Section: Introductionmentioning
confidence: 99%